Peptide-loaded dendritic-cell vaccination followed by treatment interruption for chronic HIV-1 infection: A phase 1 trial - Ide, Fuyuaki; Nakamura, Tetsuya; Tomizawa, Mariko; Kawana-Tachikawa, Ai; Odawara, Takashi; Hosoya, Noriaki; Iwamoto, Aikichi (Journal of Medical Virology, 2006)
Immune response enhanced by therapeutic HIV‐1 vaccine may control viral proliferation after discontinuation of highly active antiretroviral therapy (HAART). Although which strategies for therapeutic vaccination are feasible remains controversial, application of dendritic cells (DCs) as a vaccine adjuvant represents a promising approach to improving deteriorated immune function in HIV‐1‐infected individuals. The safety and efficacy of DC‐based vaccine loaded with HIV‐1‐derived cytotoxic T lymphocytes (CTL) peptides were thus investigated in this study. Autologous DCs loaded with seven CTL peptides with HLA‐A*2402 restriction were immunized to four HIV‐1‐infected individuals under HAART. In terms of safety, peptide‐loaded DCs were well tolerated, and only mild local and general symptoms were observed during vaccine administration. ELISPOT assays to detect IFN‐γ production in CD8+ lymphocytes revealed a limited breadth of responses to immunized peptides in two of four participants, but no response in the remaining two participants. Differences in immunological response might be attributable to the fact that responders displayed higher nadir CD4 counts before starting HAART and were immunized with a larger number of DCs per reactive peptide than non‐responders. Discontinuation of HAART after vaccination failed to lower viral set points compared to those before starting HAART. This early outcome warrants further exploration to elucidate the therapeutic value of vaccination with DCs in HIV‐1 infection. J. Med. Virol. 78:711–718, 2006. © 2006 Wiley‐Liss, Inc.